Prophylactic incisional negative pressure wound therapy reduces the risk of surgical site infection after caesarean section in obese women: a pragmatic randomised clinical trial. (7th September 2018) - Hyldig, N; Vinter, CA; Kruse, M; Mogensen, O; Bille, C; Sorensen, JA; Lamont, RF; Wu, C; Heidemann, LN; Ibsen, MH; Laursen, JB; Ovesen, PG; et al.
Abstract : Objective: To evaluate the reduction of surgical site infections by prophylactic incisional negative pressure wound therapy compared with standard postoperative dressings in obese women giving birth by caesarean section. Design: Multicentre randomised controlled trial. Setting: Five hospitals in Denmark. Population: Obese women (prepregnancy body mass index (BMI) ≥30 kg/m 2 ) undergoing elective or emergency caesarean section. Method: The participants were randomly assigned to incisional negative pressure wound therapy or a standard dressing after caesarean section and analysed by intention‐to‐treat. Blinding was not possible due to the nature of the intervention. Main outcome measures: The primary outcome was surgical site infection requiring antibiotic treatment within the first 30 days after surgery. Secondary outcomes included wound exudate, dehiscence and health‐related quality of life. Results: Incisional negative pressure wound therapy was applied to 432 women and 444 women had a standard dressing. Demographics were similar between groups. Surgical site infection occurred in 20 (4.6%) women treated with incisional negative pressure wound therapy and in 41 (9.2%) women treated with a standard dressing (relative risk 0.50, 95% CI 0.30–0.84; number needed to treat 22; P = 0.007). The effect remained statistically significant when adjusted for BMI and other potential risk factors. Incisional negative pressure wound therapy significantly reduced wound exudate whereas no difference was found for dehiscence and quality of life between the two groups. Conclusion: Prophylactic use of incisional negative pressure wound therapy reduced the risk of surgical site infection in obese women giving birth by caesarean section. Tweetable abstract: RCT: prophylactic incisional NPWT versus standard dressings postcaesarean in 876 women significantly reduces the risk of SSI. Tweetable abstract: RCT: prophylactic incisional NPWT versus standard dressings postcaesarean in 876 women significantly reduces the risk of SSI.